'Strange times to be a chicken': The meaning of a metaphor. Issue 2 (1st October 2016) - Chyutin, Dan
This article addresses Cock Fight's displacement of the Judaic metaphor of 'sacrificial chicken' onto the Palestinian, and its simultaneous reimagining of the Jew as a victimizing 'cock'. Concurrently, it discusses the problematic implications of the film's use of actual chickens as metaphors, which subverts its anti-exploitation political agenda.